Kebijakan Full Day School di Sekolah Dasar: Problematika dan Solusinya - Muhammad Iqbal Nashrulloh; Ravi Dwi Ramandhika; Yusuf Rendi Wibowo; Shaleh Shaleh (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2023)
Thiis research explains the Full Day School (FDS) policy as a solution to take advantage of children's learning time that is neglected by the family. This study used descriptive qualitative method with samples of madrasah heads and class teachers at MI Al Ma'had An-Nur. Data was collected by unstructured interviews and analyzed with the miles and hubberman model. The results showed that FDS extended a child's learning time and helped shape a positive learning environment and more in-depth material. FDS supporting factors include foundation policies, qualified human resources, support from student guardians, and encouragement to form human beings. Inhibiting factors include energy, infrastructure, cost, and experience. The school tried to overcome this by raising awareness of education personel, seeking the support of the committee and parents, and forming a JAMU TERNAMA team.